Democracy's arsenal creating a twenty-first-century defense industry - Gansler, Jacques S. (MIT Press, 2011)
New geopolitical realities -- including terrorism, pandemics, rogue nuclear states, resource conflicts, insurgencies, mass migration, economic collapse, and cyber attacks -- have created a dramatically different national-security environment for America. Twentieth-century defense strategies, technologies, and industrial practices will not meet the security requirements of a post-9/11 world. In Democracy's Arsenal, Jacques Gansler describes the transformations needed in government and industry to achieve a new, more effective system of national defense. Drawing on his decades of experience in industry, government, and academia, Gansler argues that the old model of ever-increasing defense expenditures on largely outmoded weapons systems must be replaced by a strategy that combines a healthy economy, effective international relations, and a strong (but affordable) national security posture. The defense industry must remake itself to become responsive and relevant to the needs of twenty-first-century security.